Do electronic health record prompts increase take‐home naloxone administration for emergency department patients after an opioid overdose? - Marino, Ryan; Landau, Aaron; Lynch, Michael; Callaway, Clifton; Suffoletto, Brian (Addiction, 2019)
Background and Aims: Distribution of take‐home naloxone (THN) to emergency department (ED) patients who have survived an opioid overdose (OD) could reduce future opioid mortality, but is not commonly performed. We examined whether electronic health record (EHR) prompts provided to ED physicians when discharging a patient after an OD could improve THN distribution. Design Interrupted time–series analysis to compare the percentage of OD patients who received THN during the 11 months before and after implementation of an EHR prompt on 18 June 2017. Setting and participants: A total of 3492 adult patients with diagnoses of OD discharged from nine EDs in a single health system in Western Pennsylvania from July 2016 to April 2018. Intervention and comparator: The EHR prompt was triggered by the presence of specific terms in the nurse's initial assessment note. The EHR displayed a pop‐up window during the ED physician discharge process asking the physician to consider prescribing or providing naloxone to the patient. The comparator was 'no EHR prompt'. Measurements Measurements were based on standard criteria from ICD diagnostic codes and chief complaint keywords. Findings In July 2016, 16.3% [95% confidence interval (CI) = 14.0, 18.5] of OD patients received THN, which decreased every month through June 2017 by 1.2% (P < 0.0001, 95% CI = 0.8,1.7). For each month post‐EHR prompt there was an increase of 2.8% of OD patients receiving THN (P < 0.001, 95% CI = 2.0, 3.5). No increases occurred in the ED with the highest pre‐EHR prompt THN distribution. Rates of THN distribution varied by patient age and race prior to, but not after, implementation of EHR prompts. Conclusions: Electronic health record prompts are associated with increased take‐home naloxone distribution for emergency department patients discharged after opioid overdoses.